Ms. Frizzle's adventures : medieval castle - Cole, Joanna (Scholastic Press, 2003)
When Ms. Frizzle and her student Arnold follow an underground passage beneath Craig's Castle Shop and find themselves in the middle of a siege of a 12th century English castle, they learn a great deal about both castles and the Middle Ages.